Sugar snack consumption in Ugandan schoolchildren: validity and reliability of a food frequency questionnaire - Kiwanuka SN, A ° strøm AN, Trovik TA. (Blackwell Synergy, 2006)
This study assessed the reproducibility and relative validity of an eight-item self-administered food frequency questionnaire (FFQ) on intake of sugared snacks in Ugandan schoolchildren